Error Analysis of Automatic Machine Translation on @Ajikdewa_43 Instagram Caption Posts - Putra, I Gede Arista Pramana; Agung, I Gusti Ayu Mahatma (Universitas Teknokrat Indonesia, 2024)
Instagram, one of the most popular social media platforms, is widely used by Indonesian people to connect and communicate with each other worldwide. The impact of Instagram influenced many economic sectors, such as marketing, creative industry, and personal branding. Therefore, social media is utilized through content production to gain additional income and extend engagement. One of the most commonly known Indonesian Instagram accounts is AjikDewa_43, which focuses on Balinese entertainment and non-entertainment news. Most of the posts are wrapped with general Balinese humor content supported by entertaining captions. However, due to systematic error, the automatic translation feature cannot correctly render the text into the target language of certain users. Therefore, this research aims to identify, categorize, and evaluate errors of automatic machine translation on Instagram caption posts with a case study of @Ajikdewa_43 media platform. Qualitative method with descriptive analytic approach was used to analyze the data. The data were obtained from 10 selected posts with short or long captions. Koponen’s theory of error category was applied in this study to describe the translation quality of Instagram captions. The result showed significant errors of the machine translation in identifying slang and local language as well as the contextual and grammatical meaning of the language. Several identified translation errors linked with 4 basic translation concepts were found, namely Omitted Concept (10%), Untranslated Concept (40%), Mistranslated Concept (40%), and Substituted Concept (10%).